p-systems in local Noether lattices - E. W. Johnson; Johnny A. Johnson; Monty B. Taylor (International Journal of Mathematics and Mathematical Sciences)
In this paper we introduce the concept of a p-system in a local Noether lattice and obtain several characterizations of these elements. We first obtain a topological characterization and then a characterization in terms of the existence of a certain type of decreasing sequence of elements. In addition, p-systems are characterized in quotient lattices and completions.